The Effect of Postpartum Gymnastics on the Decreased Uterine Fundal Height in Postpartum Mothers in the Work Area of the Ulaweng Health Center - Hasliana Haslan; Sulfianti Sulfianti (Newinera Publisher, 2022)
Postpartum gymnastics is exercise that mothers do after giving birth which aims to maintain and increase maternal circulation during the puerperium, as well as to help uterine involution. The purpose of this study was to determine whether there was an effect of postpartum exercise on the decrease in uterine fundal height. The type of research used in this study was quasi-experimental with a pre-test post-test control group design, to analyze the effect and differences in fundal height reduction between the intervention group and the control group. So it was determined the number of samples that met the criteria as many as 20 people. The results showed that based on the results of the mean difference test, there was a significant difference in the decrease in uterine fundal height between pre and post in the postpartum exercise group and not in the postpartum exercise group with p-value <0.05 so it can be concluded that there is an effect of postpartum exercise on the decrease in uterine fundal height. on post-partum mothers. There is an effect of postpartum exercise on the decrease in uterine fundal height in postpartum women in the Ulaweng Health Center Work Area